Aplikasi Kalman Filter untuk Memprediksi Jumlah Penderita Tuberkulosis di Indonesia - Ngatini Ngatini; Devi Indriyani (Universitas Pendidikan Ganesha, 2022)
Tuberculosis or often called tuberculosis is an infectious disease of the respiratory tract caused by the Mycrobacterium tuberculosis. To see the spread of tuberculosis in the next 5 years, calculations are needed to predict the number of tuberculosis sufferers in the next year. In solving this problem, one of the right methods to predict the number of tuberculosis sufferers in Indonesia is Kalman Filter. Kalman Filter is an algorithm used to estimate state variables in linear systems. The process carried out in measurement with Kalman Filter is the initialization of variables, the prediction stage (Time Update), and the correction stage (measurement update). To see the error rate of the prediction result, the Mean Absolute Percentage Error (MAPE) calculation is used.